Downlink beamforming in clustered cooperative multicell MIMO systems - Li, Kwok Hung (2013)
Base station cooperation has been shown to be an effective way to increase the system capacity and to suppress interference in mobile communications. A clustered multicell system is studied in this paper, where the mobile stations (MSs) will encounter intra-cluster and inter-cluster interference. By sharing the user data among base stations (BSs), one MS can be served by several BSs simultaneously, which enhances the sum rate at the MSs. The BS needs the channel state information (CSI) feedback from the MS to design its beamforming scheme. Herein, we analyze the distributed cooperation where each BS has only local CSI. A distributed beamforming technique based on the uplink-downlink duality is applied. Imperfect CSI through limited feedback is also investigated. Simulation results show that the system performance in terms of the quantized channel is close to the performance given full CSI.